7. GENETIC TESTING FOR COPY NUMBER VARIATIONS IN FIRST POLAR BODIES AND OOCYTES BY SINGLE-CELL NEXT-GENERATION SEQUENCING. (August 2019) - Sarosiak, A.; Minota, I.; Koziol, K.; Oldak, M.
Abstract : Introduction: Female meiotic errors are the main cause of whole chromosomal aneuploidy in human embryos and significantly contribute to early embryo loss. Meiotic chromosomal malsegregation occurs during divisions of the maturing oocyte in oogenesis concurrently with extrusion of two polar bodies: polar body first (PB1) and polar body second (PB2). Based on meiosis mechanism, genome of a single oocyte can be deduced by analyzing its sibling polar bodies. PB genetic testing can identify abnormalities of maternal meiotic origin and may be the only form of preimplantation genetic testing for aneuploidies (PGT-A) accepted by patients who object embryo biopsy for ideological reasons. In the majority of previous studies, array comparative genomic hybridization (aCGH) was a method of choice for comprehensive chromosome testing in polar bodies. Here, we test the use of single-cell next-generation sequencing (NGS) method in polar body testing for detecting copy number variations (CNVs) in PB1 genome and validate methods for whole genome amplification (WGA) of PB1. Material and methods: In this study, single-cell NGS technology was used to asses ploidy status of oocytes and their sibling PB1. A total of 120 single cells (60 first polar bodies and 60 oocytes) were collected from in vitro fertilization (IVF) couples and subjected for WGA using four different kits based on three distinct amplification systems: (i) polymerase chain reaction (PCR-based WGA), (ii) multiple displacement amplification (MDA) or (iii) multiple annealing and looping-based amplification cycles (MALBAC). WGA products were processed and analyzed with VeriSeq PGS MiSeq kit on MiSeq sequencing platform (Illumina) and random samples were validated with the aCGH method. Amplification uniformity and accuracy for CNV detection of the four tested kits were evaluated. Results: Ploidy status was determined for 112 of 120 (93, 3%) samples (84/112 based on direct analysis and 28/112 based on indirect analysis of the well-amplified sibling PB1 or oocyte). Estimated aneuploidy rate for the studied group which resembles the total oocyte abnormality resulting from meiosis I errors rate was 33% (37/112 samples). In the group of well-amplified PB1-oocyte pairs (33/60) a 97% concordance between the chromosomal status of PB1 and the corresponding oocyte was observed. Both whole chromosome nondisjunction (6 of 37 aneuploid samples) and abnormal chromatid pre-division and segregation were detected (31 of 37 aneuploid samples). The result is concordant with previous studies - abnormal chromatid segregation was the dominant aneuploidy-causing mechanism. Differences in WGA kits performance including amplification uniformity, aneuploidy calling potential and a number of interpretable NGS results were evaluated and the most optimal kit for PB1 genome WGA was pre-selected. Results from aCGH validation of the randomly selected samples showed full consistency with the NGS results. Conclusions: The NGS-based method used for PB1 genome analysis showed a high predictive potential of PB1 in deducing ploidy status of the corresponding oocyte and is a promising method for PGT-A of oocytes. The study also contributes to a better understanding of the chromosome segregation patterns and maternal meiosis errors. Supported by: POIR.02.03.02-14- 0092/17